Parametric Study and Characterization of Sappan Wood (Caesalpinia Sappan Linn) Natural Red Colorant Extract with Ultrasonic Assisted Extraction Method - Yuyun Yuniati; Dhiya Dini Azmi; Eric Nurandriea; Lailatul Qadariyah; Mahfud Mahfud (ASEAN Journal of Chemical Engineering, 2023)
In this study, the optimization and characterization of the colorant extraction process from sappan wood were carried out using the ultrasound-assisted extraction method. Sappan is proposed as a source of natural material wealth, producing a natural red colorant that is being needed by the community in the food sector. Based on this research, the optimum operating conditions for the extraction of sappan wood were obtained using a frequency of 40 kHz, a temperature of 60 °C, a ratio of 0.0050 g mL-1, an extraction time of 20 min, and the use of 60% ethanol solvent. Sappan wood extract created a yellow to reddish orange color at acidic pH (2-6), red at neutral pH (7) and shifted towards purplish red with increasing pH. The extract was qualitatively positive containing quinone, flavonoid, quinone, and tannin compounds, as well as several phenolic compounds detected in the Gas Chromatography Mass Spectroscopy qualitative test.